36Cl in modern groundwater dated by a multi-tracer approach (3H/3He, SF6, CFC-12 and 85Kr): a case study in quaternary sand aquifers in the Odense Pilot River Basin, Denmark - Corcho Alvarado, J.A.; Purtschert, R.; Hinsby, K.; Troldborg, L.; Hofer, M.; Kipfer, R.; Aeschbach-Hertig, W.; Arno-Synal, H. (Applied Geochemistry, 2005)
36Cl produced by thermonuclear bomb testing has been proposed as an additional tool to date or at least to identify recent groundwater components. In order to investigate the behaviour of 36Cl in shallow groundwater a multi-tracer approach (3H/3He, SF6, CFC-12 and 85Kr) was used to characterise and date the groundwater of a quaternary sands aquifer which is located on the Island of Funen near the city of Odense, Denmark. Recharge to the semi-confined shallow aquifer occurs through permeable sand windows and fractured tills at the surface. Locally, however, mixing with older pre-bomb water from the underlying limestone aquifer may occur. The integrated analyses of the available tracer data allowed a well constrained age structure determination of the investigated water system. The 36Cl/Cl ratios measured in groundwater were used to reconstruct the fallout rates for radioactive 36Cl at Odense. The calculated fallout values exceeded the fallout estimated based on data from the Dye-3 ice core in Greenland. Recycling of the bomb peak fallout seems to be the most probable reason of the high values measured. The local extent of this process is difficult to quantify, which impedes the use of 36Cl for dating.